Penerapan Model Pembelajaran Literasi Orientasi Kolaborasi dan Refleksi (LOK-R) Terhadap Kemampuan Liteasi Sains Pada Materi Fotosintesis Siswa Kelas VIII SMP Negeri 21 Maluku Tengah - Tuasamu, Yati; Lessy, Sani Yati; Hulopi, Fauzia; D, Darwin (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to describe the scientific literacy abilities of students at SMP Negeri 21 Central Maluku class VIII on photosynthesis material using the LOK-R learning model. This study is part of a study on developing learning tools to improve scientific literacy skills. Diagnosis of students' scientific literacy abilities is measured through initial and final test instruments in the form of multiple choice questions and essays. The diagnosed scientific literacy abilities are students' scientific literacy abilities before and after the LOK-R learning model is implemented which is thought to be able to develop students' scientific literacy abilities. This research includes quantitative descriptive research. The subjects of this research were 28 class VIII students of SMP Negeri 21 Central Maluku. The data collection method used is the test and questionnaire method. The data analysis technique uses quantitative descriptive analysis which refers to AKMI, 2015. The research results show that the achievement of students' scientific literacy abilities and science skills after the learning process using the LOK-R model is 100% above the 2015 EOCD target, namely above 40%. Thus, it can be concluded that the LOK-R learning model is good for developing students' scientific literacy skills.